Application of the Project Based Learning Model in the Implementation of Pancasila Values in History Learning in Phase E of High Schools in Salatiga - Angelique Yulica Dosmarohaa; Sunardi Sunardi (PT ARRUS Intelektual Indonesia, 2024)
At the same time as the implementation of Pancasila principles places an emphasis on intellectual comprehension, it also places an emphasis on the application of these values in the students' actual acts in their day-to-day lives. As a result, there is a need for a learning strategy that may aid the comprehension and implementation of Pancasila ideals in a holistic and contextual manner. Within the context of the application of Pancasila Phase E values at one of the State High Schools in Salatiga, the purpose of this study is to investigate the many ways in which the Project-Based Learning Model is used. Methods of descriptive qualitative research are used in this study. Observation, interviews, questionnaires, and documentation are the approaches that are used in the process of data collection and extraction. The findings of this study indicate that the use of the Project-Based Learning model in the process of incorporating Pancasila principles into the learning of history in phase E at one of the State High Schools in Salatiga has the potential to be an efficient learning strategy for incorporating Pancasila principles into daily life. a student. This is shown by the fact that students are able to develop high-quality projects in the form of creative movies, which are subsequently shared on social media. Additionally, students are able to provide satisfactory responses to research questionnaires, which are based on the principles of equality and social justice that are promoted by Pancasila.